Bis(selenobenzoato)dibutyltin(iv) as a single source precursor for the synthesis of SnSe nanosheets and their photo-electrochemical study for water splitting. Issue 15 (29th March 2018) - Khan, Malik Dilshad; Aamir, Muhammad; Sohail, Manzar; Sher, Muhammad; Baig, Nadeem; Akhtar, Javeed; Malik, Mohammad Azad; Revaprasadu, Neerish
Abstract : A new organo tin complex has been synthesized and used as a single source precursor for the synthesis of tin selenide nanosheets and deposition of thin films. Abstract : A new organo-tin complex has been synthesized and used as a single source precursor for the synthesis of SnSe nanosheets by the hot injection method and thin films by the aerosol assisted chemical vapor deposition (AACVD) method. The films were deposited on glass substrates at three different temperatures. The textural quality and preferential growth were found to be significantly altered by changes in the deposition temperature. Oleylamine capped nanosheets and the as-deposited thin films by AACVD were characterized by powder X-ray diffraction (p-XRD) and microscopic techniques. The thin films were also studied by Raman spectroscopy. The stoichiometry is marginally affected by temperature, and all films were slightly selenium deficient. The synthesized material was also evaluated for the photoelectrochemical (PEC) splitting of water. The PEC study revealed the bifunctional nature of the material, which can be applied for both the hydrogen evolution reaction (HER) and the oxygen evolution reaction (OER), by switching the applied potential.